2020
DOI: 10.14254/2071-789x.2020/13-3/9
|View full text |Cite
|
Sign up to set email alerts
|

Financial literacy and its variables: The evidence from Indonesia

Abstract: The purpose of this study is to investigate and measure the level of financial literacy and its variables within the academic community in Indonesia. The strength of this study is that it extends the concept of financial literacy and its variables. This study explains how members of Indonesian academic community understood their financial literacy levels and the ways in which it can be improved. The study sample comprised 889 lecturers in Indonesia. The survey method was used to measure financial literacy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 48 publications
1
31
0
11
Order By: Relevance
“…Previous research investigating financial literacy among women has revealed that financial knowledge has a weaker correlation with financial literacy than with financial attitude and behavior (Rai, Dua & Yadav, 2019). Allgood & Walstad (2011, 2016 and Dewi et al (2020) found that perceived financial literacy affects financial behavior. This finding is consistent with the findings of Mountain et al 2019) also found that the financial behavior of women in India has a stronger relationship with financial literacy than financial knowledge.…”
Section: Literature Reviewmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous research investigating financial literacy among women has revealed that financial knowledge has a weaker correlation with financial literacy than with financial attitude and behavior (Rai, Dua & Yadav, 2019). Allgood & Walstad (2011, 2016 and Dewi et al (2020) found that perceived financial literacy affects financial behavior. This finding is consistent with the findings of Mountain et al 2019) also found that the financial behavior of women in India has a stronger relationship with financial literacy than financial knowledge.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Santini et al (2019) defined the constructs of financial literacy as financial attitude, financial knowledge, and financial behavior, while Rai, Dua & Yadav (2019) defined financial literacy as the ability of individuals to make important decisions concerning effective and efficient use of money. Dewi et al (2020) proposed a financial literacy model representing the relationships between financial attitude, financial experience, financial skills, subjective financial knowledge, financial capacity, financial goals, and financial decisions. From these previous studies, it is evident that the concept of financial literacy has been defined differently and tested using various methods and frameworks (Swiecka et al 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Existe un consenso sobre el impacto favorable de la educación financiera digital en el comportamiento del gasto y del ahorro de los consumidores (Setiawan, et al, 2020;Dewi, et al, 2020). Por ejemplo, algunos autores encontraron que el uso de la tecnología digital afectaba la conducta en el gasto (Cobla y Osei-Assibey, 2018) y en el ahorro (Moenjak et al, 2020).…”
Section: Cultura Financiera Competencia Financiera Digital Y Alfabetización Financiera Digitalunclassified
“…Además de estudios en países de Latinoamérica, se han venido realizando investigaciones al respecto en otros países como en Ghana, donde Despard y Chowa (2014) testearon un modelo de medición de capacidades financieras en una muestra de adolescentes de 12 a 18 años, donde utilizaron un modelo factorial exploratorio y un confirmatorio, quedando como resultado un instrumento de 12 ítems que inicialmente era de 18, con tres dimensiones: Manejo del dinero, Conciencia de servicios financieros y Acciones de servicios financieros. Recientemente en Indonesia, Dewi et al (2020), realizaron un modelo de medición de capacidades financieras en la comunidad académica, usando un modelo de ecuaciones estructurales, que como resultado se obtuvo que las capacidades financieras son explicadas por el conocimiento financiero y las habilidades financieras, y éstas a su vez, por la conciencia financiera y la experiencia financiera, además el modelo indicó que las capacidades financieras explican a las metas financieras, al comportamiento financiero y a las decisiones financieras, el cuestionario aplicado contó con 34 preguntas y se aplicó a una muestra de 889 docentes.…”
Section: Introductionunclassified